2020
DOI: 10.33369/jeet.4.1.140-153
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Students’ Writing Skill through Technological Writing Feature of Wridea

Abstract: This study experimental research investigated the effect of using Wridea on enhancing EFL writing performance in PGRI University. It shed a light on how Wridea could enhance the writing skill. Wridea helped many of the participants to be more metacognitively aware of their English writing process. The results of this study showed that Wridea could be utilized as a service for improving the writing skill outside of the classrooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Quantitative studies (n = 28) demonstrated a positive impact or perceived positive impact of the use of digital technology-supported writing instruction on participants' overall writing skills. First, 11 studies indicated significant performance differences between students who used the technology for writing instruction and students in the control group (Adas & Bakir, 2013;Hung & Young, 2014;Khoshsima & Sayadi, 2016;Lin et al, 2018;Marleni, 2020;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Sujannah et al, 2020;Yang et al, 2019;Yu & Wang, 2016;Zaini & Mazdayasna, 2015). Second, 10 studies found that instruction incorporating DVDs/videos to support writing instruction helped participants improve their writing skills (Adas & Bakir, 2013;Chen & Su, 2012;Damavandi et al, 2018;Hsu, 2013;Kumar & Sultana, 2016;Lin et al, 2018;Noyan & Kocoglu, 2019;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Yu & Wang, 2016).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative studies (n = 28) demonstrated a positive impact or perceived positive impact of the use of digital technology-supported writing instruction on participants' overall writing skills. First, 11 studies indicated significant performance differences between students who used the technology for writing instruction and students in the control group (Adas & Bakir, 2013;Hung & Young, 2014;Khoshsima & Sayadi, 2016;Lin et al, 2018;Marleni, 2020;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Sujannah et al, 2020;Yang et al, 2019;Yu & Wang, 2016;Zaini & Mazdayasna, 2015). Second, 10 studies found that instruction incorporating DVDs/videos to support writing instruction helped participants improve their writing skills (Adas & Bakir, 2013;Chen & Su, 2012;Damavandi et al, 2018;Hsu, 2013;Kumar & Sultana, 2016;Lin et al, 2018;Noyan & Kocoglu, 2019;Soltanpour & Valizadeh, 2018a;Soltanpour & Valizadeh, 2018b;Yu & Wang, 2016).…”
Section: Tablementioning
confidence: 99%
“…For example, treatment groups which engaged in blended instruction through MOODLE, Wridea, WhatsApp, Google Classroom outperformed the control groups in writing tasks. Students in the treatment group were more involved with the learning process and better able to apply their understanding to suit their learning preferences (Adas & Bakir, 2013;Marleni, 2020;Noyan & Kocoglu, 2019;Sujannah et al, 2020). Additionally, students' writing skills improved after exposure to the interventions designed to facilitate learning to write.…”
Section: Advantages Of Digital Technology-supported Instructionmentioning
confidence: 99%
See 1 more Smart Citation
“…It encourages active learning and makes the students creative and efficient in solving problems (Stockwell, 2013). Bracewell & Sivin-Kachala & Bialo (2000) mentioned that technology has the potential to enhance students' self-concept and has a positive influence on achievements (Marleni, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In line with this, writing is seen as a non-linear, exploratory, and generative process whereby writers discover and reformulate their ideas as they attempt to approximate meaning into a paper (Manchón, 2011;Abadikhah & Yasami, 2013). Therefore, writing seems to be the most demanding skill and the fundamental basis of other language skills for EFL students to master (Marleni, 2020;Rahmawati, et al, 2020). Writing skill must be supported by reading skill because by reading a a lot, student could write their ideas (Sofyan, et al 2019;Dhillon, et al, 2020;Martina, et al, 2020) .…”
Section: A Introductionmentioning
confidence: 99%